Analisis Penggunaan Shuujoshi Joseigo oleh Kuroko Shirai pada Anime "Toaru Kagaku No Railgun" Episode 1-3 - Suarjani, Ni Ketut Nova; Adnyani, K. E. K.; Pramesti, P. D. M. Y. (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 1 (2024), 2024)
This research aims to describe the types of shuujoshi joseigo and their functions used by Kuroko Shirai in anime entitled Toaru Kagaku no Railgun in 1–3 episodes. The data were analyzed using Sudjianto (2007) & Pestemer's theory (2003). This qualitative descriptive research used listening and note-taking methods to collect the data. The results of this study are 114 data which are divided into nine types of shuujoshi joseigo used by Kuroko Shirai's character, namely 29 data of shuujoshi wa, 10 data of wane, 6 data of wayo, 53 data of no, 11 data noyo, 2 data of mono, as well as 1 data for each none, kashira, and teyo, whose functions are to soften sentences, provide information, show admiration and impression, express subtle question sentences, justify the situation, show assertiveness, express opinions, emphasize opinions, and express doubts